2023
DOI: 10.1525/collabra.73641
|View full text |Cite
|
Sign up to set email alerts
|

Sight vs. Sound Judgments of Music Performance Depend on Relative Performer Quality: Cross-cultural Evidence From Classical Piano and Tsugaru Shamisen Competitions

Abstract: Which information dominates in evaluating performance in music? Both experts and laypeople consistently report believing that sound should be the most important domain when judging music competitions, but experimental studies of Western participants rating video-only vs. audio-only versions of 6-second excerpts of Western classical performances have shown that in at least some cases visual information can play a stronger role. However, whether this phenomenon applies generally to music competitions or is restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While there has not been any work comparing written to spoken poems, or the effect of combining these two modalities, research in music has provided some hints about the differences between audio only and combined audiovisual presentations of musical performances. Prior work has looked at the effect of audio-visual information on the aesthetic and emotional appeal of musical performances (e.g., Chiba et al, 2023;Coutinho & Scherer, 2017;Pan et al, 2019;Tsay, 2013). A number of these findings suggest that the combination of audio and visual information can enhance emotional perception when compared to audio-only or visual-only presentations (Thompson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there has not been any work comparing written to spoken poems, or the effect of combining these two modalities, research in music has provided some hints about the differences between audio only and combined audiovisual presentations of musical performances. Prior work has looked at the effect of audio-visual information on the aesthetic and emotional appeal of musical performances (e.g., Chiba et al, 2023;Coutinho & Scherer, 2017;Pan et al, 2019;Tsay, 2013). A number of these findings suggest that the combination of audio and visual information can enhance emotional perception when compared to audio-only or visual-only presentations (Thompson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…That is, more recent data has indicated that when looking at musical performers of a similar quality, visual cues have been shown to help enhance and differentiate aesthetic judgements when in a competitive context (Chiba et al, 2023). When looking at visual information from musical performances, performances with high visual expressiveness were rated to be more engaging, enjoyable, and emotionally expressive when compared to performances with low visual expressiveness (Thompson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…That is, recent data has indicated that when looking at musical performers of a similar quality, visual cues have been shown to help enhance and differentiate aesthetic judgments when in a competitive context (Chiba et al, 2023). When looking at visual information from musical performances, performances with high visual expressiveness were rated to be more engaging, enjoyable, and emotionally expressive when compared to performances with low visual expressiveness (Thompson et al, 2008).…”
mentioning
confidence: 99%
“…While there has not been any work comparing written to spoken poems, or the effect of combining these two modalities, research in music can provide some hints about the differences between audio-only and combined audiovisual presentations of musical performances. Prior work has looked at the effect of audiovisual information on the aesthetic and emotional appeal of musical performances (e.g., Chiba et al, 2023; Coutinho & Scherer, 2017; Pan et al, 2019; Tsay, 2013). A number of these findings suggest that the combination of audio and visual information can enhance emotional perception when compared to audio-only or visual-only presentations (Thompson et al, 2008).…”
mentioning
confidence: 99%